Speciation, alpha diversity and extinction in neotropical ectotherms :effects of paleobiogeographic and climatic processes (2014)
"In chapter 1 we presented a case of study, the Neotropical skinks, which are difficult to identify and classify due to their conservative morphology (Miralles and Carranza, 2010). The continental populations of Mabuya distributed in Colombia have been assigned to three species: M. falconensis, M. nigropunctata, and M. mabouya. The name M. mabouya was subsequently restricted to the island nation of Dominica in the Lesser Antilles, leaving uncertain the taxonomic identity of continental populations previously assigned to this species (Miralles, 2005). To solve this problem we conducted molecular phylogenetic inference based on mitochondrial and nuclear DNA markers, combining new and previously published data. To evaluate species boundaries we employed a general mixed Yule-coalescent (GMYC) model applied to the mitochondrial data set. Our geographic sampling was especially dense in the northern Andes and Lowlands of Colombia, a central region of the distribution of this genus. Our results suggest that the diversity of Mabuya within Colombia is higher than previously recognized, and includes lineages from Central America and eastern and southern South America. Finally, we conclude that Mabuya sensu stricto should be regarded as a single, monophyletic genus, widely distributed through the Americas. In chapter 2 we were interested in evaluating whether local communities within the Neotropics are 'saturated' , or could they in theory receive even more species? We used a megadiverse group of frogs, the 'terrarana', and use a newly developed biogeographic approach to test the saturation of communities. This study used the Great American Biotic Interchange as a natural experiment. When the isthmus closed species from South America migrated to Central America and vice versa. If the concept of saturation applies, the communities that received colonists from another continent should not experience an increase in diversity (Harrison and Comell, 2008)... In chapter 3 we present the first extinction risk estimate for a tropical species based on ecophysiology. We used two species of Mabuya lizard, one distributed on the mainland and the Other one distributed in Providencia and Santa Catalina Islands. Using physiological data we estimate local extinction risk under predicted climate change within their current geographical distribution. Our study underscores the importance of estimating extinction risk of endemic species in a phylogenetic context, and using an ecophysiological model. Also, we found that a widespread species better captures the variation in potential thermal environments."